Rapid variability in the southern blazar PKS 0521-365 - Romero, Gustavo Esteban (1995)
We present an intrinsic interpretation for the recently reported radio variability in the southern blazar PKS 0521-365. A shockedjet model can account for the quasi-periodical variations in the flux density of the source by means of inhomogeneities in the electron density with a quasi-periodic distribution along a jet in which a relativistic strong shock is propagating. These inhomogeneities are naturally produced by the effects of Kelvin-Helmholtz instabilities in the hypersonic parsec scale jet. The quasi-linear evolution of the polarization position angle can be understood as an effect of the “illumination” of successive cross sections with different mean field orientation or as a consequence of the shock propagation through a turbulent region in the jet. The high brightness temperature problem introduced by the short timescale varibility is solved invocating relativistic boosting with a moderately small viewing angle in agreement with the known structure of the source. In this context, several parameters are estimated.